An Exploration of Two Competing Perspectives on Informational Contexts in Top Management Strategic Issue Interpretation - Kuvaas, Bård (Journal of Management Studies, 2002)
Two disparate theoretical views of how informational contexts affect managerial sensemaking and decision making appear in organizational research. An organizational information processing perspective posits that increasing the flow of information within and between organizations will enhance environmental awareness. In contrast, behavioural decision making and social cognition research suggest that information may increase the occurrence or magnitude of overconfidence and illusions of control. These competing predictions were examined by means of an investigation of the relationship between informational contexts and top managers’ strategic issue interpretation. Findings indicate that managers whose organizations have environmental information readily available to them perceive higher control over issues than managers in organizations with lower informational availability. Moreover, managers in top management teams with higher information processing capacity seem to perceive higher degrees of control and manageability, and search for less data in issue interpretation, than managers in teams with lower information processing capacity. These results offer some support for the behavioural decision making and social cognition perspective, and question the organizational information processing prediction that organizations engaging in active information processing are more aware of the environment and more likely to assess environmental developments, trends or events in a more vigilant manner.